Ecotoxicological evaluation of industrial port of Venice (Italy) sediment samples after a decontamination treatment - LIBRALATO, Giovanni; VOLPI GHIRARDINI, Annamaria; LOSSO C; ARIZZI NOVELLI A; CITRON M; DELLA SALA S; ZANOTTO E; CEPAK F (Environmental Pollution, 2008)
This work assesses the ecotoxicological effects of polluted sediment after a decontamination treatment process using a new sediment washing technique. Sediment samples were collected from four sites in Marghera Port industrial channels (Venice, Italy). Ecotoxicological evaluations were performed with Vibrio fischeri and Crassostrea gigas bioassays. Whole sediment and elutriate were deemed as the most suitable environmental matrices for this study. Toxicity scores developed in the Lagoon of Venice for V. fischeri on whole sediment and for C. gigas on elutriate were considered for the final ranking of samples. Ecotoxicological results showed that the treated sediment samples presented both acute and sub-chronic toxicities, which were mainly attributed to the presence of some remaining chemicals such as metals and polyaromatic hydrocarbons. The acute toxicity ranged from low to medium, while the sub-chronic one from absent to very high, suggesting that treated sediments could not be reused in direct contact with seawater.